Invasive plants in maize (Zea mays L.) cultivars under climate change scenarios in Los Ríos province, Ecuador - Sánchez Mera, María Belén (2023)
The purpose of this research is to analyze how climate change affects the spread of invasive species in maize crops in the province of Los Ríos, given that the production of this grass is crucial for the economy and food security in the region. To this end ecological niche models were generated for invasive species, Torenia crustacea and Tridax procumbens considering different climate scenarios (RCP 4.5 and 8.5) for the period 2050-2070. These analyses provide a better understanding of the significant obstacles that climate change and invasive species pose to the development and success of maize production in the region. The procedure employed included the collection of climatic and geographic data, using 288 occurrence records for Tridax procumbens and 157 for Torenia crustacea from the Biodiversity Information Facility (GBIF); Maxent software was used to evaluate models under ROC Curve and AUC criteria. It was determined that  T. crustacea and T. procumbens under the RCP 4.5 scenario presented a stability of 1,435 km² in the near future 2050 and 2,256 km² in the distant future 2070 RCP 8.5. On the other hand, its range of loss varies between 1,885 km2 and 668 km² by 2070 between the two scenarios (RCP 4.5 and 8.5). This demonstrates the magnitude of the problem of the spread of invasive species T. procumbens and T. crustacea in maize crops.